2021
DOI: 10.18821/0869-2084-2021-66-1-45-51
|View full text |Cite
|
Sign up to set email alerts
|

The microbiome of oral cavity patients with periodontitis, adhesive and biofilm forming properties

Abstract: The microbiome of oral cavity in healthy people and patients with periodontitis was analyzed to determine their adhesive properties and the ability to form biofilms. The study involved 2 groups: healthy, 18 people, and an experimental group, 20 patients with chronic generalized periodontitis moderate severity of the disease. The average age of the studied people was 35-45 years. Material - dental plaque, scraping from the mucous membrane of the back of the tongue, the contents of the periodontal groove and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 11 publications
1
6
0
2
Order By: Relevance
“…However, the results of this study also demonstrated that S. noxia may be present in a number of additional oral sites, such as the dorsum of the lingual surfaces of the mandibular incisor, and buccal surface of the maxillary molars, even if the GCF tested negative for this periodontal pathogen. Based upon these results, this may be the first description of the presence of this organism among additional oral sites, suggesting the presence of this organism at these specific biofilm locations may be more commonplace than previously though and may be similar to other studies of gram-negative periodontal pathogens that aggregate in developing or existing biofilms on teeth and the tongue [28][29][30]. In fact, recent studies have postulated that enrichment of periodontal pathogens may first occur in developing biofilm prior to the development of subgingival inflammation, gingivitis or periodontal diseasesuggesting more detailed analysis of these oral sites may be needed in future studies [31][32][33].…”
Section: Discussionsupporting
confidence: 78%
“…However, the results of this study also demonstrated that S. noxia may be present in a number of additional oral sites, such as the dorsum of the lingual surfaces of the mandibular incisor, and buccal surface of the maxillary molars, even if the GCF tested negative for this periodontal pathogen. Based upon these results, this may be the first description of the presence of this organism among additional oral sites, suggesting the presence of this organism at these specific biofilm locations may be more commonplace than previously though and may be similar to other studies of gram-negative periodontal pathogens that aggregate in developing or existing biofilms on teeth and the tongue [28][29][30]. In fact, recent studies have postulated that enrichment of periodontal pathogens may first occur in developing biofilm prior to the development of subgingival inflammation, gingivitis or periodontal diseasesuggesting more detailed analysis of these oral sites may be needed in future studies [31][32][33].…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, this study is among the first to provide an analysis and documentation of the prevalence of single-site versus multi-site SW-positive samples from an oral biorepository, similar to other initiatives that attempted to map microbial distribution and body sites for other types of medically important organisms, such as Staphylococcus aureus and Clostridium difficile [ 35 ]. Although more than half of the sites harboring this organism were traditional supragingival biofilm sites, such as the tooth biofilm of the upper buccal molar and lower lingual incisor, less obvious sites were revealed such as the biofilm from the dorsum of the tongue, which has been demonstrated in other studies to be an important intermediate site for the movement and redistribution of oral microbes [ 36 , 37 ]. In fact, this site has been recently recognized as an increasingly important site that contributes to overall microbial burden and oral ecology through various mechanisms, including salivary redistribution [ 38 , 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm characteristics may differ between diseased and healthy individuals. Chervinets and colleagues reported that the microbiota of the oral cavities of patients with periodontitis had a greater ability to adhere to the cells of the mucous membrane than those of healthy people, while their ability to form biofilms and exhibit pathogenic properties was enhanced [ 39 ].…”
Section: Discussionmentioning
confidence: 99%